2008
DOI: 10.1177/073953290802900405
|View full text |Cite
|
Sign up to set email alerts
|

Newspaper Political Blogs Generate Little Interaction

Abstract: This analysis of staff-produced blogs at 42 general circulation daily newspapers one week before the 2006 election showed that the blogs contained a small number of postings and failed to create much interaction between bloggers and readers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 1 publication
0
15
2
Order By: Relevance
“…Political bloggers ''tend to be well-educated, white middle-class'' males with an average age of ''43.3 years'' (Lawrence et al, 2009, p. 10;Dailey et al, 2008;Johnson et al, 2008;McKenna and Pole, 2008;Perlmutter, 2008). Another demographic issue concerns access to necessary infrastructure.…”
Section: Political Blogging and Deliberative Exchangesmentioning
confidence: 97%
“…Political bloggers ''tend to be well-educated, white middle-class'' males with an average age of ''43.3 years'' (Lawrence et al, 2009, p. 10;Dailey et al, 2008;Johnson et al, 2008;McKenna and Pole, 2008;Perlmutter, 2008). Another demographic issue concerns access to necessary infrastructure.…”
Section: Political Blogging and Deliberative Exchangesmentioning
confidence: 97%
“…However, researchers found that online newspapers were not taking advantage of multimedia and interactivity (Dimitrova et al, 2003). An analysis of j-blogs on 42 US daily newspaper websites revealed that j-blogs failed to create much interaction between j-bloggers and readers (Daily, Demo, & Spillman, 2008). A content analysis of 100 US online newspapers showed that media organizations used the interactive features infrequently (Schultz, 1999).…”
Section: Interactivity and The Use Of Hyperlinks And Multimediamentioning
confidence: 97%
“…Dailey, Demo, and Spillman (2008) argued that blogging does not necessarily lead to any increased interaction between bloggers and readers at all. Wallsten (2005, p. 25) critically pointed out that political blogs often merely ''act like echo chambers for mainstream media messages.''…”
mentioning
confidence: 98%